The Suitability of Smartphone LiDAR for 3D Building Information Modelling (BIM) Applications - Muhammad Ameer Adam; Noraain Mohamed Saraf; Lau Chong Luh; Mohamed Hezri Razali; Mukrimo’az Mat Hashim (International Journal of Integrated Engineering, 2024)
An entirely new realm of possibilities for three-dimensional (3D) indoor/outdoor mapping has recently emerged with the incorporation of Light Detection and Ranging (LiDAR) into smartphones. Although these new devices provide unprecedented potential for 3D scanning applications, their data quality is inferior to that of high-end LiDAR sensors. The aim of this study is to determine the capability of smartphone LiDAR in 3D building information modelling (BIM) applications. In this study, the result obtained was compared with the measurements taken using a terrestrial laser scanner (TLS) and distometer. Data acquisition was conducted using a FARO Focus laser scanner, an iPhone 13 Pro, and a distometer. The 3D BIM model was made using Autodesk Revit software. The study found that there was some distortion or drifting in the point cloud data obtained from the iPhone LiDAR. Despite the fact that some parts of the data were distorted, there are some parts of the data that were able to be used for accurate modelling. From the measurements made for BIM (windows, doors, columns, and walls) using the iPhone LiDAR, 27.27% were in the millimetre-level range, whereas 72.73% were in the centimetre-level range. In conclusion, iPhone LiDAR can be applied to 3D BIM applications.